FAKTOR - FAKTOR YANG MEMPENGARUHI TERJADINYA KATARAK DI RSUD M.M DUNDA LIMBOTO KABUPATEN GORONTALO PROVINSI GORONTALO TAHUN 2016 - Firmawati Firmawati; Rini Asnawati (-, 2021)
Cataract is muddiness that happen on the lens aye which if long continuously will cause the blind. Based on the result of survey the National of Necessity 2013, the National of Necessity rate as big as 0,4%. Cataract is caused the high of blind with the rate of happening as big as 0,1%. This research aim to know the factors that influence of cataract happen. This design of research is cross sectional. Theamountof research sample is51 respondents. The data collected with the search data, interview and questioner. The result of bivariate analyze that are all variable that examined: age, gender, job, and diabetes mellitus status that showed there has a meaning relationship with cataract happen. The result of multivariate analyze showed there has two variable most influence to the cataract happen, that is: age (p=0,000), and status DM (p=0,000). The conclusion all of variable that examined the influence of cataract happen